2021
DOI: 10.1287/mnsc.2019.3493
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Mean-Variance Analysis for Log Returns

Abstract: We propose a dynamic portfolio choice model with the mean-variance criterion for log returns. The model yields time-consistent portfolio policies and is analytically tractable even under some incomplete market settings. The portfolio policies conform with conventional investment wisdom (e.g., richer people should invest more absolute amounts of money in risky assets; the longer the investment time horizon, the more proportional amount of money should be invested in risky assets; and for long-term investment, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
47
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 47 publications
2
47
0
1
Order By: Relevance
“…Very recently, Mu et al [27] study a portfolio selection problem with both wealth-dependent risk aversion and wealth-dependent skewness preference and obtain the equilibrium investment strategy in semi-closed form. More related studies can also be found in [9,10,17,19] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Mu et al [27] study a portfolio selection problem with both wealth-dependent risk aversion and wealth-dependent skewness preference and obtain the equilibrium investment strategy in semi-closed form. More related studies can also be found in [9,10,17,19] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…In the incomplete markets with stochastic volatility, [28] considered the open-loop control framework for time-consistent mean-variance portfolio problems. A dynamic mean-variance analysis for log returns within the game-theoretic approach was proposed in [10]. Further, [13] introduced a "dynamic utility" under which the original time-inconsistent problem became a time-consistent one, and investigated possible approaches to study a general time-inconsistent optimization problem.…”
Section: Introductionmentioning
confidence: 99%
“…There also have numerous extensions of the mean-risk portfolio optimization from the single-period setting to the dynamic, continuous-time one (e.g. Zhou and Li, 2000;Bielecki et al, 2005;Jin et al, 2005;Basak and Chabakauri, 2010;He et al, 2015;Zhou et al, 2017;Gao et al, 2017;Dai et al, 2021;He and Jiang, 2021). In particular, He et al (2015) study a continuous-time mean-risk portfolio choice when risk is measured by the weighted Valueat-Risk (WVaR) but their results are rather pessimistic.…”
Section: Introductionmentioning
confidence: 99%
“…Alexander and Baptista, 2002Jin et al, 2006;Adam et al, 2008). However, there is a discrepancy between single-period and dynamic portfolio choice models, as the latter typically considers mean-risk criterion for terminal wealth; an exception is Dai et al (2021) who study continuous-time mean-variance portfolio choice for portfolio log-returns. We similarly adopt the mean-WVaR criterion for log-returns which naturally generalize the single-period return when returns are continuously compounded.…”
Section: Introductionmentioning
confidence: 99%